Field day in the semiarid region of northern Minas Gerais: management of the milk production system - Monção, Flávio Pinto; Soares, Ana Cláudia Maia; Rocha Júnior, Vicente Ribeiro; Alencar, Amanda Maria Silva; Cruz, Fernanda Naiara Fogaça da; Backsmann, Clara Francy; Silva, Ariadne Freitas; Brito, Ariane Souza de; Leal, Dijair Barbosa (Universidade Federal da Grande Dourados (UFGD), 2022)
The Meeting with Rural Producers is a tool that can be used to exchange experiences generated in the Research Centers with rural producers and field technicians. Based on the above, the objective, through the practice of the second field day, was to guide and encourage agricultural producers in the semi-arid region regarding the use of technologies strategically to improve milk production. The second field day was carried out at Sítio Boa Sorte, located in the municipality of Verdelândia, a semi-arid region in the North of Minas. The second field day was developed through technical lectures on management, production, and use of silage for dairy cattle; genetic improvement of cattle for milk production with emphasis on the semiarid region; implantation, management, and use of forage palm and BRS capiaçu grass for cattle; roughage supplementation strategies for dairy cattle; management and utilization of vaccines in cattle. There was a participation of 409 producers on the second field day, most of them belonging to the municipalities of Verdelândia, Jaíba and Janaúba. It was found that there is a demand for more field days with lectures and guidance by rural producers. It is important to continue with the lectures and technical guidance for producers in the semi-arid region of Northern Minas Gerais. The reception of this rural extension had a positive impact on milk productivity in the region. O Encontro com Produtores rurais é uma ferramenta que pode ser utilizada para trocar experiências geradas nos Centros de Pesquisas com produtores rurais e técnicos de campo. Com base no exposto, objetivou-se por meio da prática do II dia de campo orientar e incentivar produtores agropecuaristas da região semiárida quanto ao uso de tecnologias de forma estratégica visando à melhoria da produção de leite. O II dia de campo foi realizado no Sítio Boa Sorte localizado no município de Verdelândia, região semiárida do Norte de Minas. O II dia de campo foi desenvolvido por meio de palestras técnicas sobre manejo, produção e ...